2017
DOI: 10.1021/acs.chemmater.7b02196
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Host–Guest Hydrogels as Fatigue-Resistant 3D Matrix for Excessive Mechanical Stimulation of Encapsulated Cells

Abstract: Fatigue resistance of hydrogels is critical to their applications in load-bearing sites of soft tissues that are usually subjected to continuous loadings, such as joint cartilage. However, hydrogels usually swell under physiological conditions and exhibit inevitable fatigue during excessive mechanical loadings. Here we show that hydrogels cross-linked by multivalent host–guest interactions can effectively dissipate a large fraction of the loading energy (>50%) under excessive compressions (over 80% strain, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Bulk biological tissues, such as muscles, possess considerable dynamic mechanical properties, including energy dissipation through force-induced temporal rupture of secondary structures 2931 . The incorporation of elastomeric proteins or dynamic crosslinking structures has been shown to produce hydrogels with comparable energy-dissipating capacities mimicking muscles 32,33 . Developing a simple strategy to fabricate hydrogels with conformationally dynamic substructure, which allows precise tuning of the dynamic mechanical properties of the bulk material from a molecularly tailored approach, is highly desirable 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Bulk biological tissues, such as muscles, possess considerable dynamic mechanical properties, including energy dissipation through force-induced temporal rupture of secondary structures 2931 . The incorporation of elastomeric proteins or dynamic crosslinking structures has been shown to produce hydrogels with comparable energy-dissipating capacities mimicking muscles 32,33 . Developing a simple strategy to fabricate hydrogels with conformationally dynamic substructure, which allows precise tuning of the dynamic mechanical properties of the bulk material from a molecularly tailored approach, is highly desirable 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of such hydrogels to withstand high deformations has seldom been studied. To this end, researchers have explored acrylated‐β‐cyclodextrin and adamantane‐hyaluronic acid as macro‐crosslinkers of ductile polymers prepared through the polymerization of N , N ‐dimethylacrylamide monomers . This novel strategy yielded highly swollen cell‐laden hydrogels with outstanding resistance to fatigue, i.e., up to 80% compressive deformation for over 1000 cycles.…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%
“…Nonsurgical techniques are the most commonly used treatments for TMJOA and include medications, physical therapies, and occlusal splints 4,5 . Recent studies demonstrated that the supramolecular hydrogels fabricated by cross‐linked, through multivalent host‐guest interactions, are applied to the treatment of OA due to their excellent mechanical robustness 6,7 . Although OA is considered a major disease resulting in cartilage degeneration, the role of subchondral bone in the pathogenesis of OA has attracted increasing attention in recent years 8 .…”
Section: Introductionmentioning
confidence: 99%
“…supramolecular hydrogels fabricated by cross-linked, through multivalent host-guest interactions, are applied to the treatment of OA due to their excellent mechanical robustness. 6,7 Although OA is considered a major disease resulting in cartilage degeneration, the role of subchondral bone in the pathogenesis of OA has attracted increasing attention in recent years. 8 Studies have demonstrated that significant subchondral bone changes occur following cartilage degradation in the condyle of TMJOA.…”
mentioning
confidence: 99%